2021
DOI: 10.3389/fimmu.2021.670290
|View full text |Cite
|
Sign up to set email alerts
|

The Wanderings of Gut-Derived IgA Plasma Cells: Impact on Systemic Immune Responses

Abstract: Humoral immunity is mainly mediated by a B cell population highly specialized to synthesize and secrete large quantities of antibodies – the antibody-secreting cells (ASC). In the gastrointestinal environment, a mixture of foreign antigens from the diet, commensal microbiota as well as occasional harmful pathogens lead to a constant differentiation of B cells into ASC. Due to this permanent immune response, more than 80% of mammalian ASC reside in the gut, of which most express immunoglobulin A (IgA). IgA anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 82 publications
0
14
0
2
Order By: Relevance
“…Terminally differentiated plasma cells reside along the dural sinuses of mice and humans 32,91 . Interestingly, most of these plasma cells are IgA‐producers, 91 which are crucial for protection of other peripheral barrier surfaces and mucosal tissues such as the gut 98 . A recent imaging study demonstrated that IgA plasma cells residing along the dural venous sinuses increased with age and were originally educated in the gut by the microbiome 91 .…”
Section: Cns Immune Surveillance and Maintenance Of Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Terminally differentiated plasma cells reside along the dural sinuses of mice and humans 32,91 . Interestingly, most of these plasma cells are IgA‐producers, 91 which are crucial for protection of other peripheral barrier surfaces and mucosal tissues such as the gut 98 . A recent imaging study demonstrated that IgA plasma cells residing along the dural venous sinuses increased with age and were originally educated in the gut by the microbiome 91 .…”
Section: Cns Immune Surveillance and Maintenance Of Homeostasismentioning
confidence: 99%
“…32,91 Interestingly, most of these plasma cells are IgA-producers, 91 which are crucial for protection of other peripheral barrier surfaces and mucosal tissues such as the gut. 98 A recent imaging study demonstrated that IgA plasma cells residing along the dural venous sinuses increased with age and were originally educated in the gut by the microbiome. 91 These cells were shown to protect the underlying brain parenchyma from blood-borne pathogens.…”
Section: Within This Niche T Cells Can Survey Antigen-presenting Cell...mentioning
confidence: 99%
“…Protein A elicits a higher affinity for human IgG (IgG1 and IgG2) than IgM and IgA and interacts strongly with IgG2a and IgG3 compared to IgG1 in mice ( Rodrigo et al, 2015 ). However, it has been reported that colonization of commensal bacteria in humans primarily triggered the production of IgA by B cells ( Keppler et al, 2021 ). Although the binding of protein A with subclasses of antibodies in mice is not yet determined, replacement of protein A with protein L ( Rodrigo et al, 2015 ), a Peptostreptococcus magnus protein with a high affinity to representatives of most antibody classes, may be able to broadly capture different classes of antibodies including IgA in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies play a vital role in homeostasis and protective immunity at mucosal sites, as well as during systemic infections 46 , 47 , and can be divided into five isotypes, which operate in distinct places and have distinct effector functions 48 . Antibody effector functions have classically been studied in the context of pathogenic infections 49 .…”
Section: Antibody-mediated Immunity Against C Albicansmentioning
confidence: 99%